Description of four new species of genus Trechisibus Motschoulsky, 1862 from Peru - Delgado Mamani, Pedro (2020)
Four new species, belonging to genus Trechisibus Motschoulsky, 1862 are described from southeastern Peru: T. silviae sp. nov., T. elisae sp. nov., T. jorgeluisi sp. nov. and T. bravoi sp. nov. Their affinities and differences respect to other, previously known, species of the genus from the surroundings of Lake Titicaca are discussed. The way to do this task goes through a review of the taxonomic utility of characters that show certain degree of variation, such as the features of the apical triangle or the chaetotaxy of the epistoma, as well as through searching for new discriminatory features.